2017
DOI: 10.1038/nature21039
|View full text |Cite
|
Sign up to set email alerts
|

Rare and low-frequency coding variants alter human adult height

Abstract: Summary Height is a highly heritable, classic polygenic trait with ∼700 common associated variants identified so far through genome-wide association studies. Here, we report 83 height-associated coding variants with lower minor allele frequencies (range of 0.1-4.8%) and effects of up to 2 cm/allele (e.g. in IHH, STC2, AR and CRISPLD2), >10 times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (+1-2 cm/allele) compromised proteolytic inhibition of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
504
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 583 publications
(552 citation statements)
references
References 51 publications
28
504
1
8
Order By: Relevance
“…A recent study of height using exome SNP arrays and a sample size of $700,000 reported 83 height-associated coding variants with a frequency of less than 5% and effect sizes of up to 2 cm. 138 These variants each explain, on average, about the same amount of variation as common variants, whose effect sizes are of the order of 1 mm, because it is the combination of frequency and effect size that determines variation (Appendix A).…”
Section: The Presentmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of height using exome SNP arrays and a sample size of $700,000 reported 83 height-associated coding variants with a frequency of less than 5% and effect sizes of up to 2 cm. 138 These variants each explain, on average, about the same amount of variation as common variants, whose effect sizes are of the order of 1 mm, because it is the combination of frequency and effect size that determines variation (Appendix A).…”
Section: The Presentmentioning
confidence: 99%
“…With ever larger studies, the new loci identified will typically individually have smaller effect sizes (e.g., less than 0.5 mm for a trait such as height and an odds ratio of 1.01 for common disease) or, for rare variants, will be at very low frequency. 138 For disorders with population prevalence of the order of 0.1%, discovery will still be limited by experimental sample size, given that it will take many years to accumulate sample sizes of 100,000 cases or more. One challenge is how such loci can be fine-mapped or studied for mechanism.…”
Section: The Presentmentioning
confidence: 99%
“…De façon plus géné-rale, l'implication de variants rares et peu fréquents dans la composante génétique de la taille humaine est bien mise en évidence par ce travail. Il n'en reste pas moins qu'à l'issue de cet examen de près de 250 000 SNP (le contenu de l'ExomeChip) chez plus de 700 000 personnes, l'ensemble de tous les variants repérés (passés et présents) n'explique au total que 27,4 % de l'héritabilité de la taille [1]. Grâce à ce travail considérable qui a impliqué des centaines de chercheurs, on est passé d'environ 20 % à près de 30 %, un progrès certes important mais qui n'en laisse pas moins plus de 70 % d'héritabilité non expliquée : le mystère de l'héritabilité manquante n'a pas disparu.…”
Section: Une Moisson De Résultats Et Une Interrogation Persistanteunclassified
“…Un article récemment paru dans Nature [1] revient sur les déterminants génétiques de la taille de l'homme à l'âge adulte, caractère multigénique s'il en est puisque presque 700 variants qui l'influencent ont déjà été défi-nis, et montre que des variants rares dans des séquences codantes ont un impact plus important que la plupart de ceux répertoriés jusqu'ici (et qui sont en majorité des variants fréquents dans des séquences non codantes). Peut-on ainsi espérer résoudre l'irritant problème de l'héritabilité manquante (missing heritability), auquel deux chroniques ont été consacrées par le passé [2,3] (➜), et qui se manifeste dans ce cas par le fait que les 697 variants connus ne rendent compte à eux tous que de 20 % environ de l'héritabilité de la taille [4] ?…”
unclassified
See 1 more Smart Citation